Islamic belief and practices: An integrative coping approach to life problems - Embong, Rahimah; Salleh, Sakinah; Wan Yusoff, Wan Mazwati; Noruddin, Normila; Ismail, Muhamad Zaid; Mariam Nabilah, Mohd Noor; Nur Anis, Abdullah (Human Resource Management Academic Research Society, 2017)
This article provides an overview of related literature covering the wide range of issues pertaining to the problems and coping strategies in general from the Islamic worldview. There are many integrative methods and means provided in the Islamic authentic sources of the Holy Qur’an, Sunnah and the Islamic heritage as well as the modern methods. The novel aspect of this article is that apart from drawing theoretical conclusion from the existing work of coping mechanism, it is to integrate the Islamic principle pertaining to helping others in a way to address obvious inadequacies in the existing services offered to the Muslims. Therefore, it is appropriate to unearth the influence of Islamic belief and practices on man’s relationship with Allah and his relationship with mankind, on his ways of coping with the challenges and problems in his daily lives. From a review of literature, faith or belief influences the way individuals view and relate to God; and how religion in general is used to cope with difficult life circumstances. Besides that, the collaborative religious coping strategies balance an individual’s own efforts for managing stress with seeking help and support from others. Therefore, coping strategies of Muslims are approached from integrated and holistic perspective based on the understanding that man is created not from mere physical entity but also spiritual,psychological and intellectual entities. In conclusion, the Islamic coping mechanism should be planned in a way that all these dimensions of man can be better served.